Media Pembelajaran Tahfidz Surat-Surat Pendek Kelas IV Pada Madrasah Ibtidaiyah (MI) Hidayatul Athfal Jonggol - Mellinia, Mellinia; Arifin, Rita Wahyuni (Jurnal ICT : Information Communication & Technology, 2021)
Abstract-Currently technology is developing so rapidly that it often forgets the purpose of life in this world, gadgets have been attached to almost everyone, especially children who still abuse gadgets. The role of parents is very important in supervising children's activities in playing gadgets to make it more useful because most of them are only for playing games every day, plus the current condition of the teaching and learning process is online so that students and students are obliged to use gadgets. The problem behind the creation of instructional media is that grade IV students at Madrasah Ibtidaiyah (MI) Hidayatul Athfal Jonggol have difficulty memorizing short letters in the Al-Qur'an. Not a few of them often forget the order of the verses in short letters. The background factors include not using learning media that are attractive to students. This learning media contains material, Multiple Choice Quizzes, Puzzles and Profile Maker. The method used in the design of this learning media is the Multimedia Development Life Cycle (MDLC) where this method is structured based on 6 (six) stages, namely concept, design, obtaining content material, assembly, testing, and distribution. With the creation of this learning media, it is hoped that this learning media will be able to make it easier for students and students to memorize short letters with correct recitation of recitation and the memorization process will be smoother and more enjoyable.Abstrak- Saat ini teknologi berkembang sangat pesat sehingga sering melupakan tujuan hidup di dunia ini, gadget sudah melekat hampir kepada setiap orang, terutama anak-anak yang masih menyalahgunakan gadget. Peran orang tua sangatlah penting dalam mengawasi kegiatan anak dalam bermain gadget agar lebih berguna karena kebanyakan hanya untuk bermain game di setiap harinya, ditambah lagi dengan kondisi proses belajar mengajar saat ini adalah daring sehingga siswa dan siswi wajib menggunakan gadget. Permasalahan yang melatarbelakangi dibuatnya media pembelajaran adalah siswa kelas IV Pada Madrasah Ibtidaiyah (MI) Hidayatul Athfal Jonggol yang mengalami kesulitan untuk menghafal surat-surat pendek dalam Al-Qur’an. Tidak sedikit dari mereka seringkali lupa akan urutan ayat dalam surat-surat pendek. Faktor yang melatarbelakangi antara lain belum digunakannya media pembelajaran yang menarik bagi siswa. Media pembelajaran ini berisi mengenai materi, Quiz Pilihan Ganda, Puzzle dan Profil Pembuat. Metode yang digunakan dalam perancangan media pembelajaran ini adalah Multimedia Development Life Cycle (MDLC) dimana metode ini tersusun berdasarkan 6 (enam) tahapan yaitu concept, design, obtaining content material, assembly, testing, dan distribution. Dengan adanya pembuatan media pembelajaran ini diharapkan media pembelajaran ini mampu memudahkan siswa dan siswi dalam menghafal surat-surat pendek dengan bacaan tajwid yang benar serta proses menghafal menjadi lebih lancar dan menyenangkan.